Tailoring Red-to-Blue Emission in In1−xGaxP/ZnSe/ZnS Quantum Dots Using a Novel [In(btsa)2Cl]2 Precursor and GaI3 - Calem Duah; Ji-Seoung Jeong; Ji Yeon Ryu; Bo Keun Park; Young Kuk Lee; Seon Joo Lee (Molecules)
Ternary In1−xGaxP quantum dots (QDs) have emerged as promising materials for efficient blue emission, owing to their tunable bandgap, high stability, and superior optoelectronic properties. However, most reported methods for Ga incorporation into the InP structure have predominantly relied on cation exchange in pre-grown InP QDs at elevated temperatures above 280 °C. This is largely due to the fact that, when heating In and P precursors in the presence of Ga, an InP/GaP core–shell structure readily forms. Herein, we introduce a novel synthesis approach using the indium precursor [In(btsa)2Cl]2 and GaI3 to fabricate In1−xGaxP QDs in a single step at relatively low temperatures (200 °C). By adjusting the GaI3 content, we achieved controlled emission tuning from red to blue. Structural and compositional analysis through X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) confirmed successful Ga3+ incorporation into the QD core, with a corresponding blue shift in the emission as GaI3 content increased. The synthesized QDs demonstrated a photoluminescence quantum yield (PLQY) of ~50% and a full width at half maximum (FWHM) of 45~62 nm, highlighting the potential of this synthesis method for advanced optoelectronic applications.